Children’s Role in Classroom Decision-Making Dynamics: Reflections from Paulo Freire’s Pedagogy of Freedom - Erika Víquez-Zavala (Revista Electrónica Educare)
This paper presents three educational experiences in a preschool classroom as part of an action research project.  These experiences are accompanied by three types of knowledge discussed in the Pedagogy of Freedom proposed by Paulo Freire: fully listening, respect for autonomy, and adequate emotional bond.  I intend to demonstrate how 3 and 4 year-old children in a pre-kinder class (Interactive I) from a Costa Rican private school can take a leading role in the classroom decision-making process.  Methodologically, video is the only technique I used to record the scenes of classroom dynamics and systematize events.  As part of the final reflections, I state that preschool children are capable of taking a leading reflective, critical and transformative role that demands respect for their listening, independence and liberation of the self.